Notes on the taxonomy of Potamonautes obesus (A Milne-Edwards, 1868) and Potamonautes calcaratus (Gordon, 1929) (Brachyura: Potamoidea: Potamonautidae) from eastern and southern Africa - Reed, Sadie K.; Cumberlidge, Neil (Zootaxa, 2004)
The East African freshwater crab Potamonautes obesus (A Milne-Edwards, 1868) (family Potamonautidae) is redescribed from a large series of specimens from Tanzania and Somalia, and Potamon (Potamonautes) bottegoi de Man, 1898 is judged to be a junior objective synonym of P. obesus. The related taxon, Potamonautes calcaratus (Gordon, 1929) from Mozambique and South Africa, is recognised here as a valid species and is redescribed from type material. The distributions of P. obesus and P. calcaratus are described and discussed.